VIOLATION OF COOPERATIVE PRINCIPLES OF MAURICE IN THE BEAUTY AND THE BEAST MOVIE - Rani Wela Putri; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2022)
This study was created based on concerning the importance of efficient language use. The language use can be called efficient if the message is unambiguous, clear, and can be understood by both speaker and listener. This study purposes to investigate the violation of quality maxim, quantity maxim, relevance maxim and manner maxim of Grice Maurice maxim’s Cooperative Principle in the conversation of characters in Beauty and the Beast movie. In fact, there are several maxim violations that happened in human life especially figured in the movie. The maxim violation may cause misunderstanding while the conversation is going on. Descriptive qualitative method was used in this research, the data are collected from the conversation in the movie which contains coversational implicature in the character’s utterance. The result of the research shows that there is four type of maxims that are violated by Maurice’s coversation in Beauty and the Beast movie. The four type of it such as maxim of quality, maxim of quantity, maxim of relevance and maxim of manner. The result of the research shows that the maxim of quality is dominant, because the character give lacks evident, maxim quantity, maxim of relation, and maxim of manner are also violated in this movie. Keywords:  Cooperative Principles, Movie, Violation